Auditing the technical reserves of the aircraft body insurance branch and its reflection on the fairness of the financial statements : applied research in the National Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research gained its importance from the importance of technical reserves in the insurance activity and its impact on the result of the activity of insurance companies and their financial position and thus reflected on the insurance prices as the technical reserves are one of the most important and most valuable budget items usually, as well as that the insurance activity has a role in maintaining economic development where some countries develop laws and instructions for the formation of those reserves binding application to insurance companies and the fact that the financial statements in general are of interest to shareholders, banks, the General Tax Authority and other beneficiaries In the insurance activity as policyholders and the need of all these beneficiaries for reliable and credible accounting information, which makes it the auditor's responsibility to verify the integrity of measurement and disclosure of those technical reserves by obtaining reasonable assurance that the financial statements are free from material misrepresentations resulting from fraud or error، The research has reached several conclusions, the most important of which was not estimated technical reserves in accordance with the technical foundations in the insurance activity, as well as the company's non-compliance with the laws and instructions issued in this regard, and the research reached several recommendations, the most important of which is the need for the company's commitment to the technical foundations for estimating technical reserves as well as compliance with the laws and instructions issued in this regard.